UTILIZATION OF ARDUINO MICROCONTROLLER FOR PRECISE WATER SUPPLY MANAGEMENT TO ENHANCE WATER SPINACH (Ipomoea reptans Poir) GROWTH - Sanjaya, Purba; Widyastuti, R.A Diana; Manik, Tumiar Katarina; Pusvika, Niluh D. (Jurnal Agrotek Tropika, 2024)
In Indonesia, traditional methods still dominate agricultural practices, particularly in plant care and maintenance. The integration of an Arduino UNO microcontroller with a soil moisture sensor presents a significant advancement for farmers by facilitating precise soil moisture management. This study explores the application of the Arduino UNO microcontroller in the cultivation of water spinach (Ipomoea reptans Poir) under various moisture levels: 80-100%, 60-80%, 40-60%, and 20-40% of field capacity. The objectives of this research are to: (i) optimize the use of the Arduino microcontroller to enhance the growth of water spinach, (ii) evaluate the impact of different soil moisture levels on the growth of water spinach precisely regulated by the Arduino microcontroller, and (iii) identify the optimal moisture level for water spinach growth. The findings demonstrate that the Arduino microcontroller, in conjunction with the soil moisture sensor, operates effectively according to the programmed parameters, ensuring automated irrigation that meets the water requirements of water spinach. The results further indicate that varying moisture levels significantly influence the growth outcomes of water spinach, with a moisture content of 80-100% of field capacity yielding the most favorable growth and production. Additionally, water spinach plants maintained at 40-60% of field capacity produced crops suitable for marketability.